Frequency, risk and predictors of type 2 myocardial infarction hospitalizations in young obese patients: A nationwide population-based analysis in the United States. (11th May 2022) - Desai, R; Mandal, A; Peethala, MM; Raju, AR; Valdez-Aquino, C; Fatima, B; Raina, J; Itare, V; Mishra, V; Jain, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Obesity in the young population is emerging as a challenging health concern. Though there is a rising prevalence of obesity and its potential association with demand ischemia-related myocardial infarction, data remains non-existent to evaluate the association of obesity or higher body mass index (BMI) with type 2 myocardial infarction (T2MI). We aim to identify the frequency, risk and predictors of T2MI in young hospitalized obese patients compared to non-obese patients in this population-based study. Methods: We used National Inpatient Sample (2018, ICD-10 codes) to identify T2MI in young (18-44 years) hospitalized patients. Obesity was identified from comorbidities or using diagnostic codes for BMI>30 kg/m2. We performed multivariable regression analysis for the primary outcome of odds of T2MI in young obese patients compared to non-obese patients. The frequency of T2MI was compared between obese vs non-obese patients in overall and subgroup populations. Sociodemographic characteristics and comorbidities in T2MI-obese vs. T2MI-non-obese cohorts were also compared. A p<0.05 was considered a threshold for statistical significance. Results: Out of 1, 268, 255 young hospitalized patients with obesity, 555 had T2MI. T2MI was significantly higher in young obese than non-obese (44 T2MI/100000 hospitalizations in young obese patients vs. 17 T2MI/100000 hospitalizations in young non-obese patients, overall 0.04% in obese vs. 0.02% in non-obese, p<0.001). Multivariate analysis revealed higher odds of T2MI in obese than nonobese when adjusted for demographics (aOR 2.65, 95% CI:2.42-2.90, p<0.001) and social demographics with comorbidities (aOR 1.60, 95% CI:1.24-2.07, p<0.001). In young obese, higher risk was found with advancing age (OR 1.07, 95% CI 1.03-1.11, p=0.001), in males than females (aOR 2.70, p<0.001), and blacks (aOR 2.22, p=0.011) and Native Americans (OR 3.91, 95% CI: 1.13-13.49, p=0.011) vs whites. Comorbidities including chronic obstructive pulmonary disease (OR 1.86), chronic kidney disease (CKD, OR 2.36), rheumatoid arthritis/collagen vascular disease (RA/CVD, OR 3.04) Iin young obese patients independently increased the risk of T2MI hospitalizations [Table 1]. The T2MI-obese cohort had a significantly higher rate of hyperlipidemia, hypertension, diabetes, COPD, and prior history of MI and TIA/stroke compared to the T2MI-nonobese cohort [Table 2]. Conclusion: This nationwide analysis revealed a significantly higher risk of T2MI in young obese patients compared to nonobese after excluding patients with concomitant diagnoses of T1MI. Males, blacks compared to females and whites, and comorbidities including COPD, CKD and RA/CVD predicted a higher risk of T2MI in young obese patients. Future studies are warranted to evaluate the role of higher body mass index in myocardial oxygen demand-supply mismatch and short-term/long-term risk and outcomes of T2MI.